TEACHER’S PERSPECTIVE AND PROBLEM TOWARD THE SYLLABUS CONTENT IN CURRICULUM 2013 - Silvi Fitriani; Rian Sopian; Lilis Suryani (PROJECT (Professional Journal of English Education), 2020)
The curriculum in Indonesia has been adjusted overtime. It is based on the world trends demanding the curriculum be sensible for those. One of the curriculum component, the syllabus, also changes its component and content in order to support the curriculum. There are some issues in the implementation of curriculum regarding to syllabus such as different content of the syllabus, new aims of syllabus development, and the time allocation. This study is conducted in order to investigate the real teacher’s perspectives and problems toward the implementation of syllabus in Curriculum 2013. Qualitative descriptive method was used to obtain certain information. The data are gained through interview activities in order to analyze teacher’s perspective and problem occurred in syllabus. The result show that teachers have ability to recognize the syllabus required and analyze the needs for the content of syllabus. However, the setting of time allocation which is only two hours in a week did not synchroniye with the syllabus content and government preparation. All in all, this study would be eligible to provide some perspectives in syllabus content development.